Interdependence of social structure and demography in the Southern elephant seal colony of Península Valdés, Argentina - Ferrari, Mariano Andrés; Lewis, Mirtha Noemi; Pascual, Miguel Alberto; Campagna, Claudio (Marine Mammal Science)
Southern elephant seals breed at Península Valdés (PV, Argentina) along 200 km of coastline. Annual pup counts at peak breeding season for the entire colony increased from 12,113 in 1995 to 14,350 in 2006. Two demographic subunits were identified in the North and South of PV with different trends in births numbers, sex ratios and harem sizes. Birth numbers increased in the South, but decreased sharply in the North. To explain the trends in the colony and subunits, a population model was proposed that integrates social structure (harem size and sex ratio) in a fertility function that quantifies the effects of the social structure on the number of births. We found that a better fit to census data results from our model compared to a linear one (χ12 = 4.027, P = 0.045). The model was then used to test alternative hypotheses about the role of recruitment and migration on the dynamic of the two subunits. Results indicated the relevance of considering social structure in population models of gregarious and polygynous species, and is an additional tool for comparative studies between populations of elephant seals where long term census are available. Fil: Ferrari, Mariano Andrés. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Lewis, Mirtha Noemi. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Pascual, Miguel Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Campagna, Claudio. Wildlife Conservation Society; Estados Unidos. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina